Enhancing Students’ Speaking Proficiency through Storytelling Strategy - ELEPONIO, JEYFA C. (International Journal of Psychosocial Rehabilitation, 2020)
–This study was conducted based from the results of the preliminary/survey which revealed that students need to enhance their speaking proficiency skills. Through this, the researcher further conducted a study to investigate the root causes of the problems and to provide a mechanism to overcome these pressing situations through storytelling strategy. The subjects were the twenty-eight (28) BEEd third year students enrolled in English 22- Interactive English subject at College of Education. The objective of the study was to enhance students’ speaking proficiency skills through storytelling. The research design of the study was the application of Classroom Action Research (CAR) following the four steps: planning, implementation, observation and reflection. For the data collection, the following instruments were used i.e speaking test, observation and interview. The data were analyzed using qualitative and quantitative methods. Storytelling as a strategy was employed following the corresponding four-step procedure. Deciding on the teaching materials to be used, organizing of members from each group, providing video clips of story to be viewed and retelling in a form of chain and teaching students how to translate gathered responses from interviewee’s native language to second language(English) to be narrated and shared in the class. The overall result showed that students’ speaking proficiency skills were improved from pre to post intervention activity showing that story telling as a medium is an effective tool in oral communication skills of students. Furthermore, students’ speaking skills were found significantly different before and after the use of viewing and interviewing. The results of the study encouraged language instructors to strengthen the performance task as a component in evaluating the students’ communication skills which is considered a critical dimension to address. By providing varied modes of speaking activity such as debates, storytelling, extemporaneous and others, students are being trained as public speakers. Thus, enabling them to develop language fluency, comprehension, pronunciation, grammatical accuracy and vocabulary.